Promotion of pathological cardiac remodeling by excessive mitochondrial fission in physical inactivity and myocardial infarction - Masashi Miyao; Hikaru Oshima; Chihiro Kawai; Shota Furukawa; Hirokazu Kotani; Hirozo Minami; Hitoshi Abiru; Hideki Nagai; Hiromu Yanagisawa; Koh Ono; Keiji Tamaki; Yoko Nishitani (Scientific Reports)
Abstract Physical inactivity and sedentary lifestyle, including prolonged sitting, are among the most important modifiable risk factors for morbidity and mortality in myocardial infarction (MI). Recently, mitochondrial dynamics (fusion and fission) have gained considerable attention as imbalanced dynamics may play central roles in various organ injuries, including MI. This study aimed to elucidate whether imbalanced mitochondrial dynamics of cardiomyocytes are involved in physical inactivity and MI using mouse models. An MI model created by permanent coronary artery ligation showed a decreased survival rate, and the hearts of mice developed cardiac necrosis in the apex, cardiomyocyte hypertrophy, reduced ejection fraction, inflammation, and fibrosis. Ultrastructural analysis revealed increased mitochondrial fission, abnormal cardiac remodeling such as sarcomere disruption, and increased mRNA expression of cardiac injury and mitochondrial fission markers. Compared to the simple MI model, the combined physical inactivity model created by narrow cage breeding and the MI model showed a further decrease in survival rate, cardiac hypertrophy, increased mitochondrial fission in cardiomyocytes, and myofibroblast activation with cardiac fibrosis. These findings suggest that mitochondrial fission could be involved in physical inactivity and MI via abnormal crosstalk between cardiomyocytes and fibroblasts. Our study highlights the importance of developing novel mitochondrial-dynamics-rebalancing treatments in patients with MI.